Optimal Fiscal Policy in a Business Cycle Model - Chari, V. V.; Christiano, Lawrence J.; Kehoe, Patrick J. (Journal of Political Economy, 1994)
This paper develops the quantitative implications of optimal fiscal policy in a business cycle model. In a stationary equilibrium, the ex ante tax rate on capital income is approximately zero. The tax rate on labor income fluctuates very little and inherits the persistence properties of the exogenous shocks; thus there is no presumption that optimal labor tax rates follow a random walk. Most of the welfare gains realized by switching from a tax system like that of the United States to the Ramsey system come from an initial period of high taxation on capital income. Copyright 1994 by University of Chicago Press.